Understanding the role of propulsion in the prediction of front-crawl swimming velocity and in the relationship between stroke frequency and stroke length - Morais, J.E. (2022)
Introduction: This study aimed to: 1) determine swimming velocity based on a set of anthropometric, kinematic, and kinetic variables, and; 2) understand the stroke frequency (SF)-stroke length (SL) combinations associated with swimming velocity and propulsion in young sprint swimmers.Methods: 38 swimmers (22 males: 15.92 +/- 0.75 years; 16 females: 14.99 +/- 1.06 years) participated and underwent anthropometric, kinematic, and kinetic variables assessment. Exploratory associations between SL and SF on swimming velocity were explored using two two-way ANOVA (independent for males and females). Swimming velocity was determined using multilevel modeling.Results: The prediction of swimming velocity revealed a significant sex effect. Height, underwater stroke time, and mean propulsion of the dominant limb were predictors of swimming velocity. For both sexes, swimming velocity suggested that SL presented a significant variation (males: F = 8.20, p < 0.001, eta(2) = 0.40; females: F = 18.23, p < 0.001, eta(2) = 0.39), as well as SF (males: F = 38.20, p < 0.001, eta(2) = 0.47; females: F = 83.04, p < 0.001, eta(2) = 0.51). The interaction between SL and SF was significant for females (F = 8.00, p = 0.001, eta(2) = 0.05), but not for males (F = 1.60, p = 0.172, eta(2) = 0.04). The optimal SF-SL combination suggested a SF of 0.80 Hz and a SL of 2.20 m (swimming velocity: 1.75 m s(-1)), and a SF of 0.80 Hz and a SL of 1.90 m (swimming velocity: 1.56 m s(-1)) for males and females, respectively. The propulsion in both sexes showed the same trend in SL, but not in SF (i.e., non-significant variation). Also, a non-significant interaction between SL and SF was observed (males: F = 0.77, p = 0.601, eta(2) = 0.05; females: F = 1.48, p = 0.242, eta(2) = 0.05).Conclusion: Swimming velocity was predicted by an interaction of anthropometrics, kinematics, and kinetics. Faster velocities in young sprinters of both sexes were achieved by an optimal combination of SF-SL. The same trend was shown by the propulsion data. The highest propulsion was not necessarily associated with higher velocity achievement